Pengaruh Entrepreneurial Mindset dan Entrepreneurial Competence dalam Keberhasilan Usaha Kuliner Bakso Salatiga - Putri, Ayu Dewi Eka; Sirine, Hani (Ekonomis: Journal of Economics and Business, 2024)
The Covid-19 pandemic phenomenon has affected the world economy, especially the economic conditions in Indonesia. This pandemic has caused an increase in unemployment rates due to mass layoffs in order to reduce employee costs by companies during the pandemic. The micro, small and medium enterprise (MSME) sector is one of the responsibilities that society plays in economic growth. An important factor in Indonesia's economic expansion is the MSME sector. Ideas, opportunities, and business people or entrepreneurs are key components of the success of MSMEs or companies. This research aims to identify the relationship between entrepreneurial competence and business success, as well as the impact of entrepreneurial mentality. The research results found that simultaneously and partially the entrepreneurial mindset and entrepreneurial competence variables had a positive effect on the success of profits in the Salatiga Meatball Culinary business.